Esoterisme Pemikiran Gender Nasaruddin Umar - Muhammad Rusydi (AN-NISA, 2019)
Esotericism in Gender Thought Nasaruddin UmarThe dimension of esotericism in Nasaruddin Umar's gender thinking has become a style of gender thinking that is very possible to be transformed as a strategy of gender mainstreaming in the current era. The issue of gender equality expressed in its gender thinking refers to a variety of esoteric dimensions by combining the concepts of nature and form so that dependence on the text does not trap in an interpretation that is embedded in the structure of the text itself. With the esotericism of gender thinking that he developed, understanding gender issues that are more accommodating to the philosophical values of Sufism leads him to elaborate a lot of the nature of human creation as God's noble and glorified creation without having to be suppressed with issues of gender injustice.AbstrakDimensi esoterisme dalam pemikiran gender Nasaruddin Umar telah menjadi gaya berpikir gender yang sangat mungkin untuk ditransformasikan sebagai strategi pengarusutamaan gender di era saat ini. Masalah kesetaraan gender yang diekspresikan dalam pemikiran jender mengacu pada berbagai dimensi esoteris dengan menggabungkan konsep-konsep alam dan bentuk sehingga ketergantungan pada teks tidak menjebak dalam interpretasi yang tertanam dalam struktur teks itu sendiri. Dengan esoterisme pemikiran gender yang ia kembangkan, memahami isu-isu gender yang lebih akomodatif terhadap nilai-nilai filosofis tasawuf menuntunnya untuk menguraikan banyak sifat ciptaan manusia sebagai ciptaan Allah yang mulia dan mulia tanpa harus ditekan dengan masalah gender ketidakadilan.Â